Mycobacterium PPE31 Contributes to Host Cell Death - Feng, Siyuan; Hong, Zhongsi; Zhang, Guoliang; Li, Jiachen; Tian, Guo-Bao; Zhou, Haibo; Huang, Xi (Frontiers in Cellular and Infection Microbiology, 2021)
Genome scale mutagenesis identifies many genes required for mycobacterial infectivity and survival, but their contributions and mechanisms of action within the host are poorly understood. Using CRISPR interference, we created a knockdown of ppe31Mm gene in Mycobacterium marinum (M. marinum), which reduced the resistance to acid medium. To further explore the function of PPE31, the ppe31 mutant strain was generated in M. marinum and Mycobacterium tuberculosis (M. tuberculosis), respectively. Macrophages infected with the ppe31Mm mutant strain caused a reduced inflammatory mediator expressions. In addition, macrophages infected with M. marinum Δppe31Mm had decreased host cell death dependent on JNK signaling. Consistent with these results, deletion of ppe31Mtb from M. tuberculosis increased the sensitivity to acid medium and reduced cell death in macrophages. Furthermore, we demonstrate that both ppe31 mutants from M. marinum and M. tuberculosis resulted in reduced survival in macrophages, and the survivability of M. marinum was deceased in zebrafish due to loss of ppe31Mm. Our findings confirm that PPE31 as a virulence associated factor that modulates innate immune responses to mycobacterial infection.